Thinking Outside the Black Box: Current Perceptions on Breast Implant Safety and Utility. Issue 3 (23rd February 2021) - Yesantharao, Pooja S.; Lee, Erica; Khavanin, Nima; Persing, Sarah; Jenny, Hillary; Abousy, Mya; Broderick, Kristen P.; Sacks, Justin M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: There is growing public concern surrounding breast implant safety. In fact, the U.S. Food and Drug Administration recently proposed changes to breast implant labeling, which include a boxed warning. Given such efforts to increase transparency on breast implant safety, this study assessed laywomen's perceptions of breast implant safety, and the impact of proposed changes to breast implant labeling on laywomen's decision-making regarding breast implants. Methods: This was a cross-sectional investigation of women recruited through Amazon Mechanical Turk. Discrete choice modeling was used to query opinions on breast implants after viewing proposed labeling changes. Chi-square and analysis of variance were used for subgroup analyses, and McNemar analyses were used to assess changes in participants' responses. Results: The authors received 500 survey responses. At baseline, 353 participants (70.6 percent) considered breast implants to be at least somewhat safe. After viewing the proposed boxed warning, 252 participants (50.4 percent) responded that they would be less likely to receive implants. In fact, a significantly greater proportion of participants considered breast implants to be either unsafe or very unsafe after viewing suggested changes to implant labeling than at baseline (58.4 percent versus 28.8 percent; p = 0.001). By the end of the survey, willingness to consider alternative options for breast augmentation/reconstruction increased significantly from baseline. Conclusions: Improved labeling can enhance laywomen's understanding of breast implant safety and can impact decision-making. However, greater scrutiny of breast implants should not prevent women who need implants from receiving them. Transparency and objectivity in the surgeon-patient dialogue can ensure the appropriate use of medical devices such as breast implants.